The challenges of records' digitization in Malaysian public sector/ Ilylia Azuar Azmi ... [et al.] - Azmi, Ilylia Azuar; Mat Kamal, Siti Nuur-Ila; Abd Rahman, Nor Diana; Abd Jamil @ Kamarudzzaman, Azura; Ahmad, Rohayu; Timan, Hazila (Faculty of Information Management, 2021)
Digitization of information assests so called records are seen as a new strategy for nowadays organizations towards modern dynamic conconceptualized services. Due to this reason, initiatives towards records digitization in Malaysian public agencies are been structured accordingly to ensure it accomplishment. Nevertheless, only few have succeeded in realizing it. Thus, this paper is aims to examine the challenges of records digitization's works in Malaysian public sectors. Relevant literatures on records digitization in Malaysian were reviewed. The article presents that technical expertise, funding and costs, lack of specialize policy and guidelines, technological issues, poor knowledge and skills, lack of training and collaborations, low understanding of digitization as well as technical issues as the impediments to digitization projects for Malaysian public sector. The discussion brought in this paper is expected to increase the awareness and the readiness of related agencies in addressing the issues on their digitization projects.